2011
DOI: 10.1002/cjoc.201190171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Study of Some 4‐oxo‐Thiazolidine Derivatives of 2‐Aminothiazole

Abstract: Conventional and microwave assisted synthesis of new series of N-[2-{2-(substituted phenyl)-4-oxo-5-(substituted benzylidene)-1,3-thiazolidine}-iminoethyl]-2-aminothiazole 5a-5m have been developed. The cycloaddition reaction of thioglycolic acid with N-{2-(substituted benzylidenehydrazino)-ethyl}-2-aminothiazole 3a-3m in the presence of anhydrous ZnCl 2 afforded new heterocyclic compounds N-[2-{2-(substituted phenyl)-4-oxo-1,3-thiazolidine}-iminoethyl]-2-aminothiazole 4a-4m. The later product on treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the spectra of PS-AT, the characteristics bands of −NH 2 at 3411 and 3289 cm –1 disappeared, whereas a strong and broad characteristic band of secondary amine (N–H) peak at 3433 cm –1 and the antisymmetric stretching vibration band at 2924 cm –1 and symmetric stretching vibration band at 2853 cm –1 of −CH 2 groups appeared, which confirmed that the reaction between the CH 2 –Cl and −NH 2 group occurred. In addition, the ν C–N at 1358 cm –1 , ν CN at 1628 cm –1 , and ν C–S at 719 cm –1 belonging to thiazole rings also appeared in the spectra of PS-AT, which can be further confirmed by the fact that the AT ligands have grafted on the PS-Cl polymer to form PS-AT resin. …”
Section: Resultsmentioning
confidence: 73%
“…In the spectra of PS-AT, the characteristics bands of −NH 2 at 3411 and 3289 cm –1 disappeared, whereas a strong and broad characteristic band of secondary amine (N–H) peak at 3433 cm –1 and the antisymmetric stretching vibration band at 2924 cm –1 and symmetric stretching vibration band at 2853 cm –1 of −CH 2 groups appeared, which confirmed that the reaction between the CH 2 –Cl and −NH 2 group occurred. In addition, the ν C–N at 1358 cm –1 , ν CN at 1628 cm –1 , and ν C–S at 719 cm –1 belonging to thiazole rings also appeared in the spectra of PS-AT, which can be further confirmed by the fact that the AT ligands have grafted on the PS-Cl polymer to form PS-AT resin. …”
Section: Resultsmentioning
confidence: 73%
“…Once the reaction between the ligand (PABA) and PS‐Cl is finished, the intensity of absorption peak of C‐Cl at 672 cm −1 is decreased significantly. In the spectrum of PS‐PABA, the characteristic bands of ‐NH 2 (of PABA) at 3469 and 3361 cm −1 disappear, whereas a strong and broad characteristic band of secondary amine (N‐H) at 3423 and 2933 cm −1 , symmetric stretching vibration band at 2853 cm −1 of ‐CH 2 groups and symmetric stretching vibration band at 1265 cm −1 of C‐N groups appear and bands at 1694 cm −1 (C‐O) and 1432 cm −1 (‐OH) of ‐COOH of aromatic acid groups appear, which prove that the reaction between the CH 2 ‐Cl and ‐NH 2 group has occurred …”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, the PS-DU resin was characterized by the characteristic peak of CQO at 1741 cm À1 , C-N at 1604 cm À1 , and N-H at 1604 cm À1 , which is further evidence that the presence of DU is introduced to the modified polymer. [23][24][25][26][27] The characteristics and elemental analysis of the resin are shown in Table 1. The specific surface area and mean pore size are slightly changed after grafting of DU with PS-Cl.…”
Section: Characterization Of Ps-dumentioning
confidence: 99%